TANGGUNG JAWAB PRIBADI DIREKSI TERHADAP UTANG PERSEROAN (Analisis Putusan Mahkamah Agung No: 1914 K/Pdt/2009 ) - Nur Sa’adah (Universitas Pamulang, 2016)
The responsibility of Directors of the Company's debt in case of Ultra Vires exonerated from his liability if the company's debt arising from the actions of Directors had exceeded its authority as may of Directors gai as stipulated in Law No. 40 of 2007 and Articles of Association of the Company are concerned. The reasons and legal basis proposed by the Company in the principal case as contained in Decision No. 1914 K / Pdt / 2009, ie in the form of excuse the absence of consent of Commissioners to the Board of Directors in making a financing agreement with a third party, not the basis for consideration of the legal panel of judges in deciding the case in question. Thus, in the principal case, the actions of Directors, acting for and on behalf of the Company, although it did not get approval from the Commissioner did not abort their tanggungawab Company to the party entitled, so that the Company and the Board of Directors has the responsibility jointly and severally on the company's debt repayment.Keywords: Director, Corporation, Ultra Vires